A functional analysis of a natural variant of intercellular adhesion molecule-1 (ICAM-1Kilifi). - Craig, A; Fernandez-Reyes, D; Mesri, M; McDowall, A; Altieri, D; Hogg, N; Newbold, C (2000)
Intercellular adhesion molecule-1 (ICAM-1) is involved in a range of interactions both within the host and between the host and a number of pathogens. Recently we described a mutation within the coding region of the first N-terminal immunoglobulin-like domain of ICAM-1, present at high frequency within African populations, which increased the risk of cerebral malaria. To understand the mechanism by which such a polymorphism might be maintained despite counter-selection by malaria, we have carried out functional assays using both forms of ICAM-1 as soluble Fc chimeric fusion proteins. ICAM-1Kilifi has reduced avidity for LFA-1 compared with ICAM-1ref and binding to soluble fibrinogen was completely abolished with the Kilifi variant. In Plasmodium falciparum adhesion assays, ITO4-A4u binding to ICAM-1Kilifi was reduced compared with binding to the reference form. These results allow for the possibility of balanced selection between the reference and Kilifi forms of ICAM-1 through modulation of inflammatory responses and indicate the existence of differences within ICAM-1-binding P. falciparum isolates which may be relevant to pathogenesis.